DISKURSUS DISKRIMINASI GENDER DALAM TEKS LAKON LUDRUK TRENGGILING SISIK EMAS KARYA KARTOLO - Aryanti, Deny Tri; Tjahyadi, Indra (Universitas Negeri Surabaya, 2024)
This research focuses on gender discrimination contained in the text of traditional ludruk art plays developed in East Java. The purpose of this study is to describe gender discrimination contained in the text of the traditional ludruk art play that developed in East Java. Sara Mills' Critical Discourse Analysis model is used as the theoretical basis in analyzing the object. The method used in this research is descriptive qualitative method. The material object in this research is the text of the ludruk play titled Trenggiling Sisik Emas by Kartolo. The formal object in this research is the dialog in the text or discourse containing gender discrimination contained in the lakon ludruk entitled Trenggiling Sisik Emas by Kartolo. The data collection technique used in this research is literature study. Based on the research conducted, it is found that (1) characters in the subject position experience gender discrimination in the form of subordination and violence, (2) characters in the object position experience gender discrimination in the form of violence, and (3) the position of readers who are invited to side with the practice of subordination and violence against women.